Zastosowanie form morfometrycznych do analizy zróżnicowania wybranych typów powierzchni na obszarach młodoglacjalnych - Dąbrowski, Adam; Jasiewicz, Jarosław (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
This paper aims to test the possibility of using a simplified classification of land forms using principles of machine vision (geomorfons – Jasiewicz, Stepinski 2013) to analyze the types of young-glacial surface areas. In the analysis we appointed 31 test areas relevant to the 8 main types of surface (valleys bottoms, outwash plains, flat and undulated glacial moraine of small and large scale, moraine hills and edge zones). Also we run several statistical analysis to test whether different types of surface can be identified on the basis of the inventory forms. The analysis showed limited interpretiveness of the method and allowed us to identify the main reasons for those limitations. We also signaled and outlined main research directions that should be taken to remove these restrictions in the future.
Keywords: young glacial surfaces; geomorphones; machine vision; geomorphometry of lowlands